The Art of Eight Limbs: An Analysis of Muay Thai / Thai Fight Audience Loyalty - Puttarattanamane, Nopparat; Pimdee, Paitoon; Saengnoree, Amnuay; Teetakaew, Torsangrasmee (Journal of Cultural Analysis and Social Change, 2026)
This study examined factors influencing Muay Thai audience loyalty during national Thai Fight competitions. As a pillar of Thailand's global soft power strategies and a potential member of the UNESCO Intangible Cultural Heritage of Humanity list, its significance cannot be overstated. As such, the authors sampled 380 repeat Thai Fight attendees from two domestic events in 2025, probing each individual's opinions regarding service innovation (INN), social media marketing (SMM), audience motivation (MOT), and audience satisfaction (AUS) as antecedents to audience loyalty (LOY). A structural equation model was employed using the LISREL 9.1 software. The results showed that INN and SMM significantly influenced MOT and LOY, and that MOT played a strong mediating role in this relationship. In contrast, AUS did not affect LOY, indicating that emotional, cultural, and symbolic motivations are key to Thai Fight LOY rather than utilitarian satisfaction. The findings challenge traditional satisfaction-loyalty models and augment sport marketing theory by integrating perspectives on symbolic consumption and digital engagement. Additionally, our study enables sport managers and cultural policymakers to design digitally enhanced and meaningful sport experiences that cultivate LOY through shared identity, storytelling, and engagement.